Innate Immune Receptors: Key Regulators of Metabolic Disease Progression - Jin, Chengcheng; Henao-Mejia, Jorge; Flavell, Richard A. (Cell metabolism, 2013)
The study of the intersection of immunology and metabolism is a growing field fueled by the increased prevalence of obesity-associated pathologies. Importantly, the capacity of the innate immune system to sense metabolic stress induced by nutritional surplus has been linked with the progression of obesity, insulin resistance, type 2 diabetes mellitus, nonalcoholic fatty liver disease, and atherosclerosis. Moreover, it is clear that the innate immune system regulates the composition of the intestinal microbiota, which impacts multiple host metabolic processes. Here we review recent studies in this emerging field with an emphasis on how innate immune receptors determine metabolic disease progression.